Molecular and cellular origins of behavioral sex differences: a tiny little fly tells a lot - Sato, Kosei; Yamamoto, Daisuke (Frontiers in Molecular Neuroscience, 2023)
Behavioral sex differences primarily derive from the sexually dimorphic organization of neural circuits that direct the behavior. In Drosophila melanogaster, the sexdetermination genes fruitless (fru) and doublesex (dsx) play pivotal roles in producing the sexual dimorphism of neural circuits for behavior. Here we examine three neural groups expressing fru and/or dsx, i.e., the P1 cluster, aSP-f and aSP-g cluster pairs and aDN cluster, in which causal relationships between the dimorphic behavior and dimorphic neural characteristics are best illustrated. aSP-f, aSP-g and aDN clusters represent examples where fru or dsx switches cell-autonomously their neurite structures between the female-type and male-type. Processed sensory inputs impinging on these neurons may result in outputs that encode different valences, which culminate in the execution of distinct behavior according to the sex. In contrast, the P1 cluster is male-specific as its female counterpart undergoes dsx-driven cell death, which lowers the threshold for the induction of male-specific behaviors. We propose that the products of fru and dsx genes, as terminal selectors in sexually dimorphic neuronal wiring, induce and maintain the sextypical chromatin state at postembryonic stages, orchestrating the transcription of effector 3 genes that shape single neuron structures and govern cell survival and death.